Method for preparing carbon quantum dots by multistage oxidation of coal pitch
Through the multi-stage oxidation method of coal asphalt, carbon quantum dots are prepared using air, potassium ferrate solution and hydrogen peroxide, which solves the problems of environmental pollution and low fluorescent quantum yield caused by the use of strong oxidants in the prior art, and achieves a green and environmentally friendly process with high yield and high fluorescent quantum yield.
Patent Information
- Application Number
- CN202411994829.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing carbon quantum dot preparation methods require the use of a large number of strong oxidants, which leads to environmental pollution and the low yield of fluorescent quantum, limiting the large-scale production and industrial applications of fluorescent carbon quantum dots.
Coal asphalt is used as raw material to prepare carbon quantum dots by multi-stage oxidation of air preoxidation, potassium ferrate solution and hydrogen peroxide oxidation, replacing concentrated sulfuric acid, making the process simple to operate and green and environmentally friendly.
The prepared carbon quantum dots have good water solubility, strong fluorescence, high yield and fluorescence quantum yield, and are safe and environmentally friendly, reducing the cost of chemical reagents.
Smart Images

Figure BDA0005224357060000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon nanomaterials, and specifically relates to a method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch. Background Art
[0002] As a new type of carbon nanomaterial, carbon quantum dots have many advantages such as excellent photoluminescence properties, good chemical stability and large specific surface area, which makes carbon quantum dots have broad application prospects in trace substance detection, bioimaging, drug delivery, synthetic chemistry, materials science and energy storage.
[0003] Coal and coal derivatives are widely distributed, have large reserves, low prices, high carbon content and are rich in aromatic ring structures, making them ideal carbon sources for preparing carbon quantum dots. However, the complex structure of coal and its derivatives leads to uncertainty in the properties of synthesized carbon quantum dots, and how to achieve stable preparation of carbon quantum dots is a difficult problem. In addition, the existing relatively efficient carbon quantum dot preparation methods require the use of a large amount of strong oxidants, such as concentrated sulfuric acid, which can easily cause serious environmental pollution, and the resulting product generally has a low fluorescence quantum yield. The above problems greatly limit the large-scale production and industrial application of fluorescent carbon quantum dots. Summary of the invention
[0004] In order to solve the above problems in the prior art, the present invention provides a method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch. The method uses coal tar pitch as raw material, and adopts air pre-oxidation and potassium ferrate solution and hydrogen peroxide oxidation to prepare carbon quantum dots. The prepared carbon quantum dots have good water solubility and strong fluorescence, and the process is simple to operate and is green and environmentally friendly.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch, comprising the following steps:
[0007] (1) Pre-oxidation: The coal tar pitch is crushed, heated in air, and then cooled;
[0008] (2) primary oxidation: adding potassium ferrate solution to the coal tar powder pre-oxidized in step (1), reacting, filtering, washing and drying the resulting precipitate to obtain a black solid;
[0009] (3) Secondary oxidation: The black solid obtained in step (2) is added to hydrogen peroxide, filtered after the reaction to obtain a yellow filtrate, which is concentrated and freeze-dried to obtain the carbon quantum dots.
[0010] As a preferred technical solution of the present invention, in step (1), the heating is performed to 200-600° C. for 2-4 hours.
[0011] As a preferred technical solution of the present invention, in step (2), the concentration of the potassium ferrate solution is 0.8-1.2 mol / L, the pH is 4-5, and the mass ratio of coal tar powder to potassium ferrate solution is 1:(30-50).
[0012] As a preferred technical solution of the present invention, the reaction temperature in step (2) is 40 to 80° C. and the reaction time is 1 to 3 hours.
[0013] As a preferred technical solution of the present invention, in step (3), the concentration of hydrogen peroxide is 25-35wt%, and the mass ratio of black solid to hydrogen peroxide is 1:(30-60).
[0014] As a preferred technical solution of the present invention, the reaction temperature in step (3) is 40 to 80° C. and the reaction time is 1 to 4 hours.
[0015] As a preferred technical solution of the present invention, the freeze-drying temperature in step (3) is -55 to -45°C.
[0016] The present invention also provides carbon quantum dots prepared according to the above-mentioned method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The present invention uses oxidants such as air, potassium ferrate solution and hydrogen peroxide instead of concentrated sulfuric acid, the reaction conditions are mild, the process is green, environmentally friendly and safe, and the cost of chemical reagents can be greatly reduced.
[0019] (2) The carbon source used in the present invention is coal tar, which is widely available and inexpensive.
[0020] (3) The carbon quantum dots prepared by the method of the present invention have high yield and fluorescence quantum yield. DETAILED DESCRIPTION
[0021] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0022] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0023] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0024] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0025] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0026] The raw material coal tar pitch used in the following examples is Shenhua coal tar pitch, and the room temperature is 25-35° C. The following description will not be repeated.
[0027] Example 1
[0028] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0029] (1) Pre-oxidation: The coal tar pitch was crushed by a crusher and placed in a muffle furnace (air atmosphere) at 300°C. After keeping the temperature for 2 hours, it was taken out and cooled to room temperature.
[0030] (2) Primary oxidation: the coal tar powder obtained in step (1) is added to a potassium ferrate solution having a concentration of 1.0 mol / L and a pH value adjusted to 4.5 to prepare a black suspension, wherein the mass ratio of the coal tar powder to the potassium ferrate solution is 1:30. The suspension is stirred magnetically in a water bath at 50°C for 2 h. The obtained suspension is filtered, and the obtained precipitate is washed with deionized water until neutral, and dried in an oven at 50°C for 3 h to obtain a black solid.
[0031] (3) Secondary oxidation: The black solid obtained in step (2) is added to 30 wt% hydrogen peroxide, the mass ratio of the black solid to hydrogen peroxide is 1:40, and the reaction is carried out in a water bath at 50°C with magnetic stirring for 2 hours. The obtained suspension is filtered to obtain a yellow filtrate; then, the solution is rotary evaporated at 70°C for 3 hours to obtain a concentrated solution, which is freeze-dried at -50°C to a powder, namely carbon quantum dots.
[0032] The mass m1 of the pre-oxidized coal tar powder used in step (2) and the total mass m2 of the carbon quantum dots in step (3) are weighed, and the carbon quantum dot yield is calculated according to the following formula.
[0033] n=m2 / m1
[0034] Quinine sulfate solution was used as a reference substance, and the absorbance of carbon quantum dots and quinine sulfate solution was measured by UV-visible spectrophotometer to obtain the absorbance A and A of carbon quantum dots and reference substance. R Then, the fluorescence integral areas I and I of the carbon quantum dots and the reference substance were measured by a fluorescence spectrophotometer at a specific excitation wavelength (340 nm). R . Calculate the fluorescence quantum yield of the fluorescent substance to be tested according to the following formula.
[0035]
[0036] In the formula, Φ and Φ R They represent the fluorescence quantum yields of carbon quantum dots and the reference substance quinine sulfate acid solution, respectively, where the fluorescence quantum yield of the reference substance is 0.54; η and η R The refractive index of the solvent representing the acid solution of carbon quantum dots and reference substance quinine sulfate, where the refractive index of water is 1.33. In order to reduce the influence of reabsorption, when the excitation wavelength is set to 340nm, its absorbance needs to be kept below 0.1.
[0037] 1 mg of the powder obtained in step (3) was weighed and mixed with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield was 20.4% and the fluorescence quantum yield was 22.7%.
[0038] Example 2
[0039] Same as Example 1, except that, in step (3), "magnetically stirring the reaction in a water bath at 50° C. for 2 h" is modified to: "magnetically stirring the reaction in a water bath at 60° C. for 2 h".
[0040] 10 mg of the powder obtained in this example was mixed with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield was 23.2% and the fluorescence quantum yield was 26.2%.
[0041] Example 3
[0042] Same as Example 1, except that, in step (3), "magnetically stirring the reaction in a water bath at 50° C. for 2 h" is modified to: "magnetically stirring the reaction in a water bath at 70° C. for 2 h".
[0043] 10 mg of the powder obtained in this example was mixed with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield was 18.5% and the fluorescence quantum yield was 21.7%.
[0044] It can be seen from Examples 1 to 3 that with the increase of the secondary oxidation temperature, the yield and fluorescence quantum yield of the obtained carbon quantum dots first increase and then decrease. This shows that the secondary oxidation temperature has a significant effect on the yield and fluorescence quantum yield of carbon quantum dots, and the optimal secondary oxidation temperature is 60°C.
[0045] Example 4
[0046] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0047] (1) Pre-oxidation: The coal tar pitch was crushed by a crusher and placed in a muffle furnace (air atmosphere) at 200°C. After keeping the temperature for 4 hours, it was taken out and cooled to room temperature.
[0048] (2) Primary oxidation: the coal tar powder obtained in step (1) is added to a potassium ferrate solution having a concentration of 0.8 mol / L and a pH value adjusted to 4 to prepare a black suspension, wherein the mass ratio of the coal tar powder to the potassium ferrate solution is 1:40. The suspension is stirred magnetically in a water bath at 80°C for 1 h. The obtained suspension is filtered, and the obtained precipitate is washed with deionized water until neutral, and dried in an oven at 50°C for 3 h to obtain a black solid.
[0049] (3) Secondary oxidation: The black solid obtained in step (2) is added to 25 wt% hydrogen peroxide, the mass ratio of the black solid to hydrogen peroxide is 1:60, and the mixture is reacted in a water bath at 80°C with magnetic stirring for 1 hour. The resulting suspension is filtered to obtain a yellow filtrate; then, the solution is rotary evaporated at 70°C for 4 hours to obtain a concentrated solution, which is freeze-dried at -55°C to a powder, namely, carbon quantum dots.
[0050] Weigh 1 mg of the powder obtained in step (3) and mix it with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield is 17.3% and the fluorescence quantum yield is 21.3%.
[0051] Example 5
[0052] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0053] (1) Pre-oxidation: The coal tar pitch was crushed by a crusher and placed in a muffle furnace (air atmosphere) at 600°C. After keeping the temperature for 3 hours, it was taken out and cooled to room temperature.
[0054] (2) Primary oxidation: the coal tar powder obtained in step (1) is added to a potassium ferrate solution having a concentration of 1.2 mol / L and a pH value adjusted to 5 in advance to prepare a black suspension, wherein the mass ratio of the coal tar powder to the potassium ferrate solution is 1:50. The suspension is magnetically stirred in a water bath at 60°C for 3 h. The obtained suspension is filtered, and the obtained precipitate is washed with deionized water until it becomes neutral, and dried in an oven at 50°C for 3 h to obtain a black solid.
[0055] (3) Secondary oxidation: The black solid obtained in step (2) is added to 35 wt% hydrogen peroxide, the mass ratio of the black solid to hydrogen peroxide is 1:30, and the mixture is reacted in a water bath at 40°C with magnetic stirring for 4 hours. The resulting suspension is filtered to obtain a yellow filtrate; then, the mixture is rotary evaporated at 70°C for 4 hours to obtain a concentrated solution, which is freeze-dried at -45°C to a powder, namely carbon quantum dots.
[0056] Weigh 1 mg of the powder obtained in step (3) and mix it with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield is 18.7% and the fluorescence quantum yield is 27.7%.
[0057] Comparative Example 1
[0058] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0059] (1) Primary oxidation: Coal tar pitch was crushed with a pulverizer, and the obtained coal tar pitch powder was added to a potassium ferrate solution with a concentration of 1.0 mol / L and a pH value of 4.5 to prepare a black suspension. The mass ratio of coal tar pitch powder to potassium ferrate solution was 1:30. The mixture was magnetically stirred in a 50°C water bath for 2 h. The obtained suspension was filtered, and the obtained precipitate was washed with deionized water until neutral, and dried in an oven at 50°C for 3 h to obtain a black solid.
[0060] (2) Secondary oxidation: The black solid obtained in step (1) is added to 30 wt% hydrogen peroxide, the mass ratio of the black solid to hydrogen peroxide is 1:40, and the reaction is carried out in a water bath at 50°C with magnetic stirring for 2 h. The obtained suspension is filtered to obtain a yellow filtrate; then, the solution is rotary evaporated at 70°C for 3 h to obtain a concentrated solution, which is freeze-dried at -50°C to a powder, namely carbon quantum dots.
[0061] Weigh 1 mg of the powder obtained in step (2) and mix it with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield is 17.3% and the fluorescence quantum yield is 21.3%.
[0062] Comparative Example 2
[0063] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0064] (1) Pre-oxidation: The coal tar pitch was crushed by a pulverizer and placed in a muffle furnace at 300°C. Oxygen was introduced and the mixture was kept in an oxygen atmosphere for 2 h before being taken out and cooled to room temperature.
[0065] (2) Primary oxidation: the coal tar powder obtained in step (1) is added to a potassium ferrate solution having a concentration of 1.0 mol / L and a pH value adjusted to 4.5 to prepare a black suspension, wherein the mass ratio of the coal tar powder to the potassium ferrate solution is 1:30. The suspension is stirred magnetically in a water bath at 50°C for 2 h. The obtained suspension is filtered, and the obtained precipitate is washed with deionized water until neutral, and dried in an oven at 50°C for 3 h to obtain a black solid.
[0066] (3) Secondary oxidation: The black solid obtained in step (2) is added to 30 wt% hydrogen peroxide, the mass ratio of the black solid to hydrogen peroxide is 1:40, and the reaction is carried out in a water bath at 50°C with magnetic stirring for 2 hours. The obtained suspension is filtered to obtain a yellow filtrate; then, the solution is rotary evaporated at 70°C for 3 hours to obtain a concentrated solution, which is freeze-dried at -50°C to a powder, namely carbon quantum dots.
[0067] Weigh 1 mg of the powder obtained in step (3) and mix it with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield is 19.0% and the fluorescence quantum yield is 23.9%.
[0068] Comparative Example 3
[0069] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0070] (1) Pre-oxidation: The coal tar pitch was crushed by a crusher and placed in a muffle furnace (air atmosphere) at 180°C. After being kept warm for 2 hours, it was taken out and cooled to room temperature.
[0071] (2) Primary oxidation: the coal tar powder obtained in step (1) is added to a potassium ferrate solution having a concentration of 1.0 mol / L and a pH value adjusted to 4.5 to prepare a black suspension, wherein the mass ratio of the coal tar powder to the potassium ferrate solution is 1:30. The suspension is stirred magnetically in a water bath at 50°C for 2 h. The obtained suspension is filtered, and the obtained precipitate is washed with deionized water until neutral, and dried in an oven at 50°C for 3 h to obtain a black solid.
[0072] (3) Secondary oxidation: The black solid obtained in step (2) is added to 30 wt% hydrogen peroxide, the mass ratio of the black solid to hydrogen peroxide is 1:40, and the reaction is carried out in a water bath at 50°C with magnetic stirring for 2 hours. The obtained suspension is filtered to obtain a yellow filtrate; then, the solution is rotary evaporated at 70°C for 3 hours to obtain a concentrated solution, which is freeze-dried at -50°C to a powder, namely carbon quantum dots.
[0073] 10 mg of the powder obtained in this comparative example was mixed with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield was 22.5%, and the fluorescence quantum yield was 25.3%.
[0074] Comparative Example 4
[0075] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0076] (1) The coal tar pitch was crushed by a crusher and placed in a muffle furnace (air atmosphere) at 300°C, kept at this temperature for 2 hours, and then taken out and cooled to room temperature;
[0077] (2) The coal tar powder obtained in step (1) is added to 30 wt% hydrogen peroxide, the mass ratio of coal tar powder to hydrogen peroxide is 1:40, and the mixture is reacted in a water bath at 50° C. with magnetic stirring for 2 h. The resulting suspension is filtered to obtain a yellow filtrate; the mixture is then rotary evaporated at 70° C. for 3 h to obtain a concentrated solution, which is freeze-dried at -50° C. to a powder, namely carbon quantum dots.
[0078] Weigh 1 mg of the powder obtained in step (2) and mix it with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield is 18.1% and the fluorescence quantum yield is 19.1%.
[0079] Comparative Example 5
[0080] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0081] (1) Pre-oxidation: The coal tar pitch was crushed by a crusher and placed in a muffle furnace (air atmosphere) at 300°C. After keeping the temperature for 2 hours, it was taken out and cooled to room temperature.
[0082] (2) Primary oxidation: the coal tar powder obtained in step (1) is added to a potassium ferrate solution having a concentration of 1.0 mol / L and a pH value adjusted to 8 in advance to prepare a black suspension, wherein the mass ratio of the coal tar powder to the potassium ferrate solution is 1:30. The suspension is stirred magnetically in a water bath at 50°C for 2 h. The obtained suspension is filtered, and the obtained precipitate is washed with deionized water until it is neutral, and dried in an oven at 50°C for 3 h to obtain a black solid.
[0083] (3) Secondary oxidation: The black solid obtained in step (2) is added to 30 wt% hydrogen peroxide, the mass ratio of the black solid to hydrogen peroxide is 1:40, and the reaction is carried out in a water bath at 50°C with magnetic stirring for 2 hours. The obtained suspension is filtered to obtain a yellow filtrate; then, the solution is rotary evaporated at 70°C for 3 hours to obtain a concentrated solution, which is freeze-dried at -50°C to a powder, namely carbon quantum dots.
[0084] 10 mg of the powder obtained in this example was mixed with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield was 19.1% and the fluorescence quantum yield was 21.0%.
[0085] Comparative Example 6
[0086] Carbon quantum dots were prepared by a multi-stage oxidation method using coal tar pitch as a carbon source. The steps are as follows:
[0087] (1) Pre-oxidation: The coal tar pitch was crushed by a crusher and placed in a muffle furnace (air atmosphere) at 300°C. After keeping the temperature for 2 hours, it was taken out and cooled to room temperature.
[0088] (2) Primary oxidation: the coal tar powder obtained in step (1) was added to 30 wt % hydrogen peroxide, with the mass ratio of coal tar powder to hydrogen peroxide being 1:40, and the mixture was stirred under magnetic stirring in a water bath at 50° C. for 2 h. The obtained suspension was filtered, and the obtained precipitate was dried in an oven at 50° C. for 3 h to obtain a black solid;
[0089] (3) Secondary oxidation: The black solid obtained in step (2) is added to a potassium ferrate solution having a concentration of 1.0 mol / L and a pH value adjusted to 4.5 in advance to prepare a black suspension, wherein the mass ratio of the black solid to the potassium ferrate solution is 1:30. The suspension is magnetically stirred in a water bath at 50°C for 2 h, and the resulting suspension is filtered to obtain a yellow filtrate. The suspension is then rotary evaporated at 70°C for 3 h to obtain a concentrated solution, which is freeze-dried at -50°C to a powder, namely, carbon quantum dots.
[0090] Weigh 1 mg of the powder obtained in step (3) and mix it with water to prepare a carbon quantum dot solution with a concentration of 1 mg / L. The carbon quantum dot yield is 20.8% and the fluorescence quantum yield is 19.1%.
[0091] From the comparison between Comparative Example 1 and Example 1, it can be seen that adding high-temperature air for pre-oxidation before formal oxidation can effectively increase the yield of carbon quantum dots and can also improve the fluorescence quantum yield to a certain extent.
[0092] From the comparison between Comparative Example 2 and Example 1, it can be seen that changing the pre-oxidation atmosphere from air to pure oxygen reduces the yield of carbon quantum dots and increases the yield of fluorescent carbon quantum dots.
[0093] It can be seen from the comparison between Comparative Example 3 and Example 2 that: within a certain range, the yield and fluorescence quantum yield of carbon quantum dots decrease as the pre-oxidation temperature decreases.
[0094] From the comparison between Comparative Example 4 and Example 1, it can be seen that removing the primary oxidation will reduce the yield and quantum yield of the final product. The primary oxidation and the secondary oxidation in the multi-stage oxidation method have their own effects, which will affect the characteristics of the final product to a certain extent.
[0095] From the comparison between Comparative Example 5 and Example 1, it can be seen that without changing other reaction conditions, only changing the pH value of the oxidation reaction once and adjusting it to alkaline will reduce the yield and fluorescence quantum yield of carbon quantum dots. Under slightly acidic conditions, potassium ferrate has stronger oxidizability, and the yield and quantum yield of the carbon quantum dot product are better.
[0096] From the comparison between Comparative Example 6 and Example 1, it can be seen that the exchange of the primary oxidation and secondary oxidation conditions will also affect the characteristics of the carbon quantum dots to a certain extent. The final yield does not change much, but the fluorescence quantum yield decreases significantly. The reason may be that the Fe 3+ related.
[0097] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch, characterized in that: The following steps are involved: (1) Pre-oxidation: The coal tar pitch is crushed, heated in air, and then cooled; (2) primary oxidation: adding potassium ferrate solution to the coal tar powder pre-oxidized in step (1), reacting, filtering, washing and drying the resulting precipitate to obtain a black solid; (3) Secondary oxidation: The black solid obtained in step (2) is added to hydrogen peroxide, filtered after the reaction to obtain a yellow filtrate, which is concentrated and freeze-dried to obtain the carbon quantum dots.
2. The method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch according to claim 1, characterized in that: In step (1), the heating is performed at 200-600° C. for 2-4 hours.
3. The method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch according to claim 1, characterized in that: In step (2), the concentration of the potassium ferrate solution is 0.8-1.2 mol / L, the pH is 4-5, and the mass ratio of coal tar powder to potassium ferrate solution is 1:(30-50).
4. The method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch according to claim 1, characterized in that: The reaction temperature in step (2) is 40-80° C. and the reaction time is 1-3 h.
5. The method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch according to claim 1, characterized in that: In step (3), the concentration of hydrogen peroxide is 25-35wt%, and the mass ratio of black solid to hydrogen peroxide is 1:(30-60).
6. The method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch according to claim 1, characterized in that: The reaction temperature in step (3) is 40-80° C. and the reaction time is 1-4 h.
7. The method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch according to claim 1, characterized in that: The freeze-drying temperature in step (3) is -55 to -45°C.
8. Carbon quantum dots prepared according to the method for preparing carbon quantum dots by multi-stage oxidation of coal tar pitch according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation of carbon quantum dots based on coal tar asphalt and detection method for HCHO
CN106566542A
Method for preparing energy band-controllable carbon quantum dots by taking coal as raw material
CN109437154A
Preparation method and application of coal-based asphaltene high-efficiency conversion carbon quantum dots
CN115872390A
Asphalt-based carbon negative electrode material and two-step pre-oxidation synthesis preparation method and application thereof
CN118479454A
Production method of carbon quantum dot composite body, production method of carbon quantum dot-containing solution, and production method of carbon quantum dot
JP2022147418A